Nursing care of children : principles and practice - James, Susan Rowen ;Nelson, Kristine Ann ;Ashwill, Jean Weiler (London, United Kingdom : Elsevier Health Sciences, 2013)
Master the art of caring for children with most effective, efficient, and affordable title on pediatric nursing care. Taking on a family focus, this student-friendly text teaches growth, development, and information on the major body system alterations. Plus, dramatically streamlined content and new learning tools make this new edition even more tailored to your learning needs. Expert reviews of chapter content ensure all chapters include current practices, terms, and updated information.
Unit I: Introduction to child health nursing -- Unit II: Growth and development : the child and the family -- Unit III: Special considerations in caring for children -- Unit IV: Caring for children with health problems --
Includes bibliographical references and index.
Keywords: PEDIATRIC NURSING -- METHODS